2012
DOI: 10.5120/5049-7463
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Separated Solitary Waves Solution for KDV Equation through Finite Element Technique

Abstract: The Present manuscript reports the solution of well known non linear wave mechanics problem called KDV equation, here main emphasis is given on the Mathematical modeling of traveling waves and their solutions in the form of Kortewegde Vries equation (KdV) It is a non-linear Partial Differential Equation (PDE) of third order which arises in a number of physical applications such as water waves, elastic rods, plasma physics etc. We present numerical solution of the above equation using B-spline FEM (Finite Eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The version employed herein is a variational formulation which has met with considerable success in recent years in simulating many complex fluid flows. These include thermal radiation-convection micropolar flow [34], mixed convection micropolar flow [35], magneto-hemodynamic non-Newtonian flow [36], nanofluid mechanics [36][37][38] and free surface wave hydrodynamics [39]. In order to apply finite element method first we assume .…”
Section: Variational Finite Element Computational Solutionsmentioning
confidence: 99%
“…The version employed herein is a variational formulation which has met with considerable success in recent years in simulating many complex fluid flows. These include thermal radiation-convection micropolar flow [34], mixed convection micropolar flow [35], magneto-hemodynamic non-Newtonian flow [36], nanofluid mechanics [36][37][38] and free surface wave hydrodynamics [39]. In order to apply finite element method first we assume .…”
Section: Variational Finite Element Computational Solutionsmentioning
confidence: 99%
“…So many methods and approaches have been made to find the approximate analytic solutions and numerical solutions of KdV equations, such as Adomian Decomposition Method (ADM) [1], Variation Iteration Method (VIM) [1], Homotopy Perturbation Method (HPM) [1], Homotopy Perturbation Method using Elzaki Transform [2], Homotopy Perturbation Method using Laplace Transform [3], Adomian Decomposition Method using Elzaki Transform [4], Numerical solutions to a linear KdV equation on unbounded domain [5], The numerical solutions of KdV equation using radial basis functions [6], Numerical solution of separated solitary waves for KdV equation through finite element technique [7].…”
Section: Introductionmentioning
confidence: 99%
“…by Canıvar et al in [17]. A study based on cubic B-spline finite element method for the solution of the KdVE is suggested by Kapoor et al [18]. A Bubnov-Galerkin finite element method with quintic B-spline functions taken as element shape and weight functions is presented for the solution of the KdVE [19].…”
Section: Introductionmentioning
confidence: 99%